The Right to Language Assistance in Italian Criminal Proceedings - Patrizia Anesa; Federica Cantagalli (Iperstoria)
Court interpreting plays a critical role in ensuring effective communication during legal proceedings. This study explores issues related to language assistance services in Italian legal proceedings, focusing on the Direttissime division at the Milan Courthouse. Qualitative data were gathered through interviews with interpreters and professionals working at the courthouse as well as direct observations conducted in 2023. The interviews revealed systemic issues, including inadequate training, lack of legal expertise, and poor remuneration. Observations of courtroom proceedings also highlighted significant gaps in interpreter performance and organization, often compromising the defendant’s understanding and participation. Notwithstanding the inherent constraints of a singular case study, this analysis corroborates the notion that, despite the implementation of legal reforms, there has been minimal advancement in enhancing the quality of interpretation over recent decades. Therefore, this work calls for better training, assessment, and remuneration for interpreters, alongside more collaborative efforts among legal stakeholders to uphold the right to a fair trial for non-native speakers.